2019
DOI: 10.1111/adb.12783
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol inhibits sucrose self‐administration by CB1 and CB2 receptor mechanisms in rodents

Abstract: A growing number of studies suggest therapeutic applications of cannabidiol (CBD), a recently U.S. Food and Drug Administration (FDA)–approved medication for epilepsy, in treatment of many other neuropsychological disorders. However, pharmacological action and the mechanisms by which CBD exerts its effects are not fully understood. Here, we examined the effects of CBD on oral sucrose self‐administration in rodents and explored the receptor mechanisms underlying CBD‐induced behavioral effects using pharmacologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 97 publications
2
26
0
Order By: Relevance
“…Actually, the inhibition of the POMC gene expression following CBD and CBG treatment is consistent with their putative role as negative allosteric modulators of CB1 receptor [30]. In contrast, the inhibition of the expression of the NPY gene registered after the treatment, although being consistent with the anorexigenic effects ascribed to CBD [6], appears to be discrepant with the orexigenic role of CBG [16,17]. This result is, however, in agreement with the expression of the CB1 receptor on synaptic endings innervating both NPY and POMC first order neurons in the hypothalamus [29,31].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Actually, the inhibition of the POMC gene expression following CBD and CBG treatment is consistent with their putative role as negative allosteric modulators of CB1 receptor [30]. In contrast, the inhibition of the expression of the NPY gene registered after the treatment, although being consistent with the anorexigenic effects ascribed to CBD [6], appears to be discrepant with the orexigenic role of CBG [16,17]. This result is, however, in agreement with the expression of the CB1 receptor on synaptic endings innervating both NPY and POMC first order neurons in the hypothalamus [29,31].…”
Section: Discussionsupporting
confidence: 64%
“…The endocannabinoid-mediated activation of CB1 and CB2 has long been implicated in the onset of neuroprotective effects, whereas the neuroprotection occurring after phyto-cannabinoid administration could be better explained by a multitarget mechanism involving different receptor systems, including peroxisome proliferator-activated receptors (PPARs) and transient receptor potential (TRP) channels [3][4][5]. CB1 and CB2 receptors were considered as promising targets for the development of anti-obesity drugs [6] as well, to the point that the rimonabant, the prototype of the of CB1 blockers, was clinically employed for a short period (more than ten years ago) for its anorexigenic effects. Nevertheless, the rimonabant was soon after retired from the market for an increased frequency in psychiatric disorders following the treatment [7].…”
Section: Introductionmentioning
confidence: 99%
“…We found that systemic administration of CBD (10, 20, and 40 mg/kg, i.p.) produced a dose-dependent reduction in sucrose self-administration in rats and in wild-type (WT) mice [ 52 ]. Unexpectedly, CBD was more efficacious in transgenic CB1 receptor-knockout (CB1-KO) mice than in WT mice.…”
Section: Cbd Attenuates Cocaine Addictive-like Behavior By the Cb1mentioning
confidence: 99%
“…The ∆9-tetrahydrocannabinol (THC) has long been considered the sole psychotropic molecule, but a novel phytocannabinoid, the ∆9-tetrahydrocannabiphorol, which is even more potent than THC itself, was recently identified in C. sativa phytocomplex [2]. Cannabidiol (CBD) is another terpenophenol that has long been studied from a pharma-toxicological point of view [3][4][5][6]. Despite having a chemical structure very close to that of the THC, CBD was reported to act with a different multitarget mechanism, including the binding to more than 60 receptor proteins.…”
Section: Introductionmentioning
confidence: 99%